2022
DOI: 10.3390/healthcare10091749
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Online Healthcare Community Usage: A Grounded Theory Approach

Abstract: The online healthcare community has grown rapidly in recent years. However, the antecedents and consequences of the use of online healthcare community platforms have not been systematized. Using grounded theory, this study collects first-hand data on the use of online healthcare communities through in-depth interviews and analyzes the interview data using a three-level coding approach including open coding, axial coding, and selective coding. The results showed the following. (1) Doctors, hospitals, and the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Question items and measures were drawn from earlier studies. Among these was doctor-patient communication, including five measure items, taken from Ha and Longnecker ( 13 ) and Wang et al ( 11 ). The doctor-patient relationship was measured with included five measurement items revised from Zhang et al ( 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Question items and measures were drawn from earlier studies. Among these was doctor-patient communication, including five measure items, taken from Ha and Longnecker ( 13 ) and Wang et al ( 11 ). The doctor-patient relationship was measured with included five measurement items revised from Zhang et al ( 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al ( 11 ) found that doctor-patient communication includes six main sub-categories: emotional attitude, mode, adequacy, efficiency, content similarity, and communication service quality. The use of online healthcare communities has a positive impact on doctor-patient communication, as it can improve the degree of communication and patient satisfaction, as well as meeting patients’ expectations of consultation ( 11 ). Other studies have confirmed parts of these conclusions.…”
Section: Research Hypotheses and Model Proposalmentioning
confidence: 99%
See 3 more Smart Citations